Healthy Lifestyle and Anthropometric Measurements among Employed Women: The Women\'s Health Initiative - Batoul Ahmadi; Mohammad Azmal; Leila Janani; Mahtab Bayatrizi; Fatemeh Nooghani (Tehran University of Medical Sciences, 2017)
Background and Aim: The cornerstone of primary prevention is adopting a healthy lifestyle including abstaining from smoking, maintaining appropriate body weight and appropriate eating habits. The aim of the study was to clarify anthropometric and healthy lifestyles measurements among the working women. Materials and Methods: The cross sectional study was conducted in 2014. A total of 682 working women at TUMS voluntarily participated in this study. The data collecting tool was Womenchr('39')s Health initiative checklist (SABA) consisted of two parts anthropometric and lifestyle indices, were developed and validated by MOHME. Descriptive and analytic statistics was used for analyzing data. Results: Most of the participants were on a diet (%88.1) in the past year. In general, women did not have satisfactory healthy eating habits. Vegetable consumption was only 47/6% and 52% took soft drinks and ate fast foods. Regarding physical activity only 28% of women had proper physical activities. Data for Body Mass Index (BMI) showed that less than half of them were overweight or obese, and 42% with central obesity.  Conclusion: According to findings of this study. Anthropometric indices and lifestyle for working women is far from satisfactory condition and make potential risks for their health, which needs to be improved. Establishing training programs and facilities for women to adopt healthy lifestyle including eating habits, and daily physical activity, not only can promote their health, but also improves their personal, family and social performances along with enhancing public health culture.